Deskripsi dan fenomena yang terjadi pada perkawinan alami sapi Peranakan Ongole (PO) dengan sapi Bali di Kandang Percobaan Loka Penelitian Sapi Potong - Jauhari Efendy; Frediansyah Firdaus (Livestock and Animal Research, 2021)
Objective: To determine the natural mating behavior pattern of PO bulls with Bali cows in the cattle breeding system using freestall housing of “Litbangtan Model”.Methods: The materials were 63 livestock; 3 PO bulls and 60 Bali cows. The study was designed with a randomized block design (RBD) with three treatments based on the physiological status of Bali cows; namely Treatment A: 20 heifers, Treatment B: 10 heifers and 10 cows, and Treatment C: 20 cows. The parameters observed were the pattern of estrous behavior, the length of time from estrus to mating, the phenomena that occurred during pregnancy and the birth process, and the pregnancy rate.Results: The estrous intensity in the +++ category was higher than + or ++ in all treatments. The shortest average time interval between estrus and mating occurred in treatment A with a pregnancy rate of 83.33%. The phenomena that occur during pregnancy and at birth are abortion, dystocia and calf death at birth. Abortion occurs at 4-6 months of gestation, dominated by heifers; the incidence of dystocia is entirely experienced by heifers.Conclusion: Cows with estrus were 86.67% with various expressions starting from silent heat (+), medium (++) and visible (+++). There are 42 Bali cows that show normal behavior in a series of reproductive activities (estrus and mating) with a time interval estrus and mating between 0.67-14.75 hours. Pregnancy rate 83.33%; the phenomena that occur during pregnancy and childbirth include abortion, calf death at birth and dystocia.